Analysis of the Effect of Work Stress, Work Load and Work Environment on Teacher Performance at TRI Karya Sunggal School Deli Serdang - Sovia Delviana Br Kaban; Kholilul Kholik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the influence of work stress, workload, and work environment on teacher performance at Tri Karya Sunggal School, Deli Serdang Regency. The background of this study is based on the importance of the role of teachers in improving the quality of education, which is greatly influenced by the psychological conditions and work environment they experience. The method used in this study is a quantitative approach. Samples were taken purposively from 50 permanent teachers at Tri Karya Sunggal School. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression to determine the simultaneous and partial effects of each independent variable on teacher performance. The results of the analysis showed that work stress, workload, and work environment simultaneously had a significant effect on teacher performance. Partially, work stress had a negative and significant effect, workload had a negative but not significant effect, while the work environment had a positive and significant effect on teacher performance. These findings indicate that improving teacher performance requires attention to managing work stress and creating a conducive work environment. This study recommends that schools conduct workload management evaluations and build psychosocial support systems for educators.